2011
DOI: 10.1016/j.ijrobp.2010.07.1977
|View full text |Cite
|
Sign up to set email alerts
|

Consideration of Dose Limits for Organs at Risk of Thoracic Radiotherapy: Atlas for Lung, Proximal Bronchial Tree, Esophagus, Spinal Cord, Ribs, and Brachial Plexus

Abstract: Purpose To review the dose limits and standardize the three-dimenional (3D) radiographic definition for the organs at risk (OARs) for thoracic radiotherapy (RT), including the lung, proximal bronchial tree, esophagus, spinal cord, ribs, and brachial plexus. Methods and Materials The present study was performed by representatives from the Radiation Therapy Oncology Group, European Organization for Research and Treatment of Cancer, and Soutwestern Oncology Group lung cancer committees. The dosimetric constrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
214
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(215 citation statements)
references
References 33 publications
0
214
0
1
Order By: Relevance
“…The organs at risk are normal lung tissue, spinal cord, brachial plexus, pulmonary artery, heart, esophagus, and the proximal bronchial tree (21,22). We can assume that the complication probabilities of OARs other than the proximal bronchial tree are negligible for both tumors whether a single or fractionated schedule is employed.…”
Section: Resultsmentioning
confidence: 99%
“…The organs at risk are normal lung tissue, spinal cord, brachial plexus, pulmonary artery, heart, esophagus, and the proximal bronchial tree (21,22). We can assume that the complication probabilities of OARs other than the proximal bronchial tree are negligible for both tumors whether a single or fractionated schedule is employed.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, with patients experiencing longer overall survival rates in this new era of viralinduced carcinoma, efforts to reduce the dose to normal tissue structures, like the brachial plexus, will be of greater importance to limit risks of brachial plexopathy and other late effects of therapy. One limitation of our study is the lack of tumor HPV status, which has been shown to be associated with improved progression-free and overall survival in oropharyngeal squamous cell carcinoma [14,20]. We did, however, have data on tobacco smoking history, which is inversely correlated with HPV status and has also been independently associated with progression-free and overall survival.…”
Section: Discussionmentioning
confidence: 92%
“…For SBRT, the volume characteristics and tumor localization will be more critical 22. Additional constraints for normal tissues need to be added for large dose fraction size, such as chest wall, esophagus, big blood vessels, and bronchial tree 23. These were not directly investigated in this study.…”
Section: Discussionmentioning
confidence: 99%